MARITIME MUSEUMS VS SEAPORT MUSEUMS NAVIGATING THE EVOLUTION FROM MARITIME PORT BUSINESS TO THE MARITIME TOURISM INDUSTRY - SELVADURAY, MAHENDRRAN; BANDARA, YAPA MAHINDA; YUNUS, NORHASLINDA (Journal of Maritime Logistics, 2023)
Ocean-based countries has more advantages compare to a landlock regions where there face challenges on the access to the oceanography activities. Beyond major maritime trading and transportation business, maritime tourism business is one of the economically contributing sectors for coastal region nations. The main aim of this paper is to (a) identify the role of seaport museum and maritime museum, (b) to explore the benefits of seaport museum and maritime museum towards seaport industry, (c) proposing a framework for the future research direction on seaport tourism as a complementary business opportunity for seaport industry. Bibliometric analysis technique was adopted with VoS viewer, and a content analysis on 30 research articles were performed to derive the results and then coded with NVivo 12 software. The result shows that, there are nine key measurement factors needed to be considered to archive the objectives. Seaport museum and maritime museum are not the same, whereas maritime museum only focuses on all the sea-based artifacts while seaport museum focuses on the specific sea-based artifacts which are in the port limits. Moreover, both the museums encourage the port city development and have a high impact to the seaport revenue generation.